Heat adaptation towards improve survival of Bifidobacterium longum BB536 during the spray drying of Sudanese fermented Medida - Mohammed Kabeir, Barka; Mustafa, Shuhaimi; Wong, Stephenie Yoke Wei; Saari, Nazamid; Abd Manap, Mohd Yazid (Academic Journals, 2009)
This study examined the survival of Bifidobacterium longum BB 536 following the spray drying and during the storage of Medida, a fermented Sudanese cereal porridge. Medida was produced using 225 g flour of two days malted brown rice; blended in 0.405 L distilled water and cooked in 1 L boiling water. 150 g skim milk was added followed by sterilization; and the mixture was inoculated with B. longumBB536 and incubated until the biomass reached approximately 9 Log CFU/ml. Spray drying inlet temperature was regulated at 160oC. The strain BB536 survivability at different outlet temperatures (95, 85, and 75ºC), powder rehydration times (15 and 30 min) and mild heat adaptations (50 and 45ºC) prior to spray drying were evaluated. The viable count at 95ºC outlet temperature recorded only 2.48 Log CFU/g but improved to 4.28 ± 0.30 log CFU due to decrease outlet temperature to 85oC. Using 45oC heat adaptation for 30 min and 85oC outlet temperature, high viability of 7.82 ± 0.30 Log CFU/g meeting the requirement of probiotic foods was attained. Moreover, the population obtained did not reveal any significant cells reduction during 60 days refrigeration storage showing survivability maintenance of 88.31%. Therefore, the current investigation demonstrated that development of fermented probiotic Medida powder from malted brown rice flour is possible employing suitable outlet temperature and heat adaptation.